2013
DOI: 10.1128/jvi.02733-12
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Enterovirus 71 RNA-Dependent RNA Polymerase Complexed with Its Protein Primer VPg: Implication for a trans Mechanism of VPg Uridylylation

Abstract: g Picornavirus RNA replication is initiated by VPg uridylylation, during which the hydroxyl group of the third tyrosine residue of the virally encoded protein VPg is covalently linked to two UMP molecules by RNA-dependent RNA polymerase (RdRp; also known as 3D pol ). We previously identified site 311, located at the base of the palm domain of the enterovirus 71 (EV71) RdRp, to be the site for EV71 VPg binding and uridylylation. Here we report the crystal structure of EV71 3D pol complexed with VPg. VPg was anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 45 publications
1
74
0
Order By: Relevance
“…One possible explanation of how VPg could be uridylylated at this site is that the nucleotidylylation reaction is carried out by a second molecule of 3D pol (59, 103, 151). Such a “trans” uridylylation mechanism was supported also from structural studies of the EV71 polymerase complexed with VPg, in which VPg bound at the bottom of the palm domain could not access the catalytic site (27). It should be noted, however, that a front-loading model of VPg-binding and a “ cis ” uridylylation mechanism was proposed for FMDV 3D pol (43) and for the RNA polymerase of rhinovirus (7).…”
Section: Initiation Of Protein-primed Picornavirus Rna Synthesismentioning
confidence: 83%
See 1 more Smart Citation
“…One possible explanation of how VPg could be uridylylated at this site is that the nucleotidylylation reaction is carried out by a second molecule of 3D pol (59, 103, 151). Such a “trans” uridylylation mechanism was supported also from structural studies of the EV71 polymerase complexed with VPg, in which VPg bound at the bottom of the palm domain could not access the catalytic site (27). It should be noted, however, that a front-loading model of VPg-binding and a “ cis ” uridylylation mechanism was proposed for FMDV 3D pol (43) and for the RNA polymerase of rhinovirus (7).…”
Section: Initiation Of Protein-primed Picornavirus Rna Synthesismentioning
confidence: 83%
“…Three dimensional structures have been reported for several members of the virus family such as PV, HRV14, CVB3, FMDV, EV-71 (7, 27, 43, 44, 59, 61). The 3D pol of Picornaviridae are 460-470 amino acids long and possess high primary sequence similarity and structural homology (26).…”
Section: Factors Involved In the Initiation Of Protein-primed Rna mentioning
confidence: 99%
“…The EV genome contains a single-stranded positive-sense polyadenylated RNA of approximately 7,400 nucleotides (10). Translation of the single open reading frame is initiated by ribosomes that use an internal ribosomal entry site located in the 5= untranslated region (UTR) region of the viral genome and gives rise to a polyprotein of approximately 250 kDa (11)(12)(13)(14). This polyprotein is further processed into four structural proteins (VP1 to VP4) to form the viral capsid and seven structural proteins (2A to 2C and 3A to 3D) by two viral proteases (2A and protease 3C [3C pro ]), together with a protease precursor, 3CD (15).…”
mentioning
confidence: 99%
“…This suggests that the VPg bound at this site in 3D pol cannot be uridylylated by the carrier 3D pol , which raises the possibility of an intermolecular uridylylation reaction in which two molecules of 3D pol are required for VPgpUpU synthesis (Tellez et al, 2006;Gruez et al, 2008). In recent studies using EV-71, a similar model for intermolecular uridylylation has been proposed (Chen et al, 2013;Sun et al, 2012). In earlier studies, mutations in the VPg binding site on the back of PV1 3D pol were shown to inhibit 3AB binding to 3D pol (Hope et al, 1997;Lyle et al, 2002).…”
Section: Discussionmentioning
confidence: 94%